The value of forest recreation in Azorean public parks - Lopes,Fernando (2021)
Abstract: This study assesses the aggregated value of demand for forest recreation in the Azores using a regional travel cost model. Previous assessments of total economic value (TEV) of the Portuguese forest by Mendes (2005) and INCF (2006) consider both market services and non-market services. Non-timber benefits (NTB) such as recreation, carbon sequestration, protection of soil, and biodiversity were valued using value transfer methodologies. Forest recreation accounts for 0.65% of TEV using a unit transfer value of 2.75 Euros/per visit estimated by Loureiro and Albiac (1996). The present primary study assesses the value of forest recreation in the Azorean islands instead of a single site approach. A count data travel-cost model, taking into account characteristics of data from on-site face-to-face interviews, is used instead of contingent valuation. This study uses data from a survey of visitors to public forest parks in São Miguel, Terceira, and Pico. Visits to public forest parks are a significant component of forest recreation, attracting more than 18% of residents with an average of five trips per year. The typical visitant is male, 38 years of age, and has secondary education. Those interviewed engage in physical activities, walking and running, as well as picnics, an opportunity to meet friends and family during the summer. The profile of this summer visitors changes to a more hard engagement in running and walking activities during autumn and spring. 33% of visitors are fully satisfied with their visiting experience and the quality of public forest parks. The value of a daily visit is 13.66 euros, and the total economic value exceeds 3 million euros in all Azorean parks for 275 thousand visitors. A conservative assessment of the benefit of forest recreation is higher than the total market value of wood production.